2022
DOI: 10.1111/ced.15141
|View full text |Cite
|
Sign up to set email alerts
|

Different types of emollient cream exhibit diverse physiological effects on the skin barrier in adults with atopic dermatitis

Abstract: Background. Eczema (atopic dermatitis; AD) is a very common itchy skin condition affecting 1 in 5 children and up to 1 in 10 adults worldwide. The skin of eczema sufferers is prone to redness, irritation and dryness because it does not form an effective barrier, i.e. the ability of the skin to stop irritants, allergens and microorganisms getting into the body. Skin barrier dysfunction is a hallmark of AD. The regular and liberal (600 g/week for an adult) use of emollients is recommended for all patients with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…35 The IPD included 35 Not all emollients are the same in terms of their effects on the skin barrier. 37 It is still possible that some emollients could reduce or delay AD development as the role of epithelial barrier disruption in the development of allergic disorders is quite convincing. 38 Perhaps barrier enhancement would work in a low-risk rather than high-risk population or perhaps only when combined with enhanced skin care such as reduced bathing and soap avoidance, but the evidence for benefit so far has been disappointing.…”
Section: Interpretation In Context With Other Studiesmentioning
confidence: 99%
“…35 The IPD included 35 Not all emollients are the same in terms of their effects on the skin barrier. 37 It is still possible that some emollients could reduce or delay AD development as the role of epithelial barrier disruption in the development of allergic disorders is quite convincing. 38 Perhaps barrier enhancement would work in a low-risk rather than high-risk population or perhaps only when combined with enhanced skin care such as reduced bathing and soap avoidance, but the evidence for benefit so far has been disappointing.…”
Section: Interpretation In Context With Other Studiesmentioning
confidence: 99%
“…In addition, a moisturizer helps to maintain and restore skin flexibility by blocking the evaporation of moisture, and induces uniform exfoliation of old dead skin cells to maintain a smooth skin surface [ 6 ]. When the moisturizer functions properly in the skin, the skin maintains homeostasis despite changes in the external environment, so that the stratum corneum can maintain proper hydration [ 7 ]. After applying a moisturizer to damaged skin, the skin barrier is restored through the four-step process that follows [ 8 ].…”
Section: The Role Of Moisturizers In the Skin Barriermentioning
confidence: 99%
“…Various factors can affect the effectiveness of the emollient, such as the type of emollient, the number of times of application, and the start time, so it is difficult to conclude yet. A new large randomized controlled trial, Prevention of Eczema by a Barrier Lipid Equilibrium Strategy (PEBBLES), which controlled for these factors, is currently underway [ 7 , 74 ].…”
Section: Selection Of Basic Cosmetics For Individual Skin Diseasesmentioning
confidence: 99%
“…Several studies 12,17–26 have also investigated the prophylactic effect of the early emollient application on the development of AD in infants; however, the early application of emollients for the prevention of AD is currently being debated 27–30 . More importantly, a recent study reported that different types of emollient cream exhibit diverse physiological effects on the skin barrier in AD subjects 31 …”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] More importantly, a recent study reported that different types of emollient cream exhibit diverse physiological effects on the skin barrier in AD subjects. 31 Therefore, we performed this systematic review and network meta-analysis to answer two questions as follows: (a) whether the early application of emollients in infancy can effectively prevent the later development of AD and (b) which types of emollients may be the optimal option for preventing the development of AD in infants.…”
mentioning
confidence: 99%